2018
DOI: 10.1021/acs.joc.7b03017
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Radical Cascades to Synthesize Difluoroalkylated Pyrrolo[1,2-a]indoles

Abstract: We disclose herein a photocatalytic difluoroalkylation and cyclization cascade reaction of N-(but-2-enoyl)indoles with broad substrate scopes in up to 90% isolated yield. This method provides sustainable and efficient access to synthesize difluoroalkylated pyrrolo[1,2-a]indoles with a quaternary carbon center under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Several other general fluoroalkylation/cascade cyclization reactions were reported where BrCF 2 P(O)(OEt) 2 was used in the context of other fluoroalkylating reagents. These reports include phosphoryldifluoromethylation of 4‐phenylpent‐4‐enoic acid ( 9 ) (Pan, Han and co‐workers; [55] later extended to a series of ω‐unsaturated carboxylic acids by Yang and co‐workers [56] ), N ‐(but‐3‐enoyl)indole 11 (Li and co‐workers [57] ), and 2‐( N ‐trifluoroacetyl‐ N ‐benzylamino)phenylacetylene ( 13 ) (Zhong, Tong and co‐workers [58] ), as well as carboxylative phosphoryldifluoromethylation of N ‐benzyl‐2‐phenylallylamine ( 15 ) (Yu and co‐workers [59] ) with subsequent intramolecular cyclizations of the corresponding intermediate radical species yielding CF 2 ‐phosphonate‐containing γ‐butyrolactone 10 , pyrrolo[1,2‐a]indole 12 , dibenzazepine 14 and oxazolidinone 16 , respectively (Scheme 5). Interesting use of radical clock as a synthetic method was reported by Xu, Lan, and co‐workers.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Several other general fluoroalkylation/cascade cyclization reactions were reported where BrCF 2 P(O)(OEt) 2 was used in the context of other fluoroalkylating reagents. These reports include phosphoryldifluoromethylation of 4‐phenylpent‐4‐enoic acid ( 9 ) (Pan, Han and co‐workers; [55] later extended to a series of ω‐unsaturated carboxylic acids by Yang and co‐workers [56] ), N ‐(but‐3‐enoyl)indole 11 (Li and co‐workers [57] ), and 2‐( N ‐trifluoroacetyl‐ N ‐benzylamino)phenylacetylene ( 13 ) (Zhong, Tong and co‐workers [58] ), as well as carboxylative phosphoryldifluoromethylation of N ‐benzyl‐2‐phenylallylamine ( 15 ) (Yu and co‐workers [59] ) with subsequent intramolecular cyclizations of the corresponding intermediate radical species yielding CF 2 ‐phosphonate‐containing γ‐butyrolactone 10 , pyrrolo[1,2‐a]indole 12 , dibenzazepine 14 and oxazolidinone 16 , respectively (Scheme 5). Interesting use of radical clock as a synthetic method was reported by Xu, Lan, and co‐workers.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…A wide array of the substrate bearing electron‐donating groups as well as electron‐withdrawing groups were amendable with the reaction affording the corresponding products in good to excellent yields (Scheme 28). [100] Irradiated by visible light, the photocatalyst [Ir 3+ ] transfers to an excited state that is subsequently oxidized by BrCF 2 CO 2 Et to give the CF 2 CO 2 Et radical. The addition of radical to the double bond produces intermediate.…”
Section: Difluoroalkylation and Intramolecular Cyclization Reactionmentioning
confidence: 99%
“…[36][37][38][39][40][41] In 2018, the Li group demonstrated that difluoroalkylated pyrrolo [1,2-α]indoles with a quaternary carbon center can be efficiently synthesized via difluoroalkylation and cyclization cascade reaction of N-(but-2-enoyl)indoles with BrCF 2 R (Scheme 1). 42 In the presence of visible light, products with good to high yields were generated. A plausible reaction mechanism is outlined in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%